Epidemiology and Clinical Outcomes of Cardiac Arrhythmias in Pulmonary Arterial HypertensionTake-Home Points - Thanaboon Yinadsawaphan, MD; Mustafa Suppah, MD; Srekar N. Ravi, MD; Juan M. Farina, MD; Robert L. Scott, MD, PhD; Dan Sorajja, MD (CHEST Pulmonary)
Background: Cardiac arrhythmias can exacerbate symptoms and potentially lead to death in patients with pulmonary hypertension. However, there is limited evidence regarding the impact of cardiac arrhythmias in patients with pulmonary arterial hypertension (PAH). Research Question: What are the prevalence, incidence, and impact of arrhythmias in patients with PAH? Study Design and Methods: In a retrospective cohort study including 512 patients with PAH from 2001 to 2021 at 3 Mayo Clinic sites, demographic data at PAH diagnosis and clinical outcomes over a 10-year period were collected. The patients with PAH were categorized into 3 groups based on arrhythmic onset: (1) patients with arrhythmia before PAH diagnosis, (2) patients diagnosed with arrhythmia during PAH follow-up, and (3) patients without arrhythmia during PAH follow-up. Survival outcomes were analyzed using multivariable Cox proportional hazards regression, adjusted with the REVEAL 2.0 risk score. Results: Among the 512 patients with PAH (mean age, 56.1 years; 81.8% female), the prevalence of cardiac arrhythmias at PAH diagnosis was 10.5%, consisting of atrial fibrillation (7%), atrial flutter (2%), and supraventricular tachycardia (0.8%). The cumulative incidences of new-onset arrhythmias at 1, 5, and 10 years were 6%, 18%, and 29%, respectively. Patients with arrhythmia diagnosed before and after PAH diagnosis exhibited significantly higher all-cause mortality rates with adjusted hazard ratio of 2.06 (95% CI, 1.36-3.12) and 1.57 (95% CI, 1.17-2.20), respectively. Similarly, both arrhythmic groups demonstrated shorter median time to the first all-cause hospitalization (9.5 and 15.9 vs 21.2 months) and a higher number of all-cause hospitalizations (0.38 and 0.64 vs 0.10 times per year) compared with the nonarrhythmic group. Interpretation: Our results demonstrate that cardiac arrhythmias can develop in nearly one-third of patients with PAH within 10 years of PAH diagnosis and independently contribute to increased hospitalization frequency and mortality, in addition to the current REVEAL 2.0 risk score.